Magnitude and duration of excess of post‐exercise oxygen consumption between high‐intensity interval and moderate‐intensity continuous exercise: A systematic review. (12th July 2020) - Panissa, Valéria L. G.; Fukuda, David H.; Staibano, Victor; Marques, Marcelo; Franchini, Emerson
Summary: The present systematic review examined the effect of exercise intensity (high‐intensity interval exercise [HIIE] vs. moderate‐intensity continuous exercise [MICE] vs. sprint interval exercise [SIE]) on excess post‐exercise oxygen consumption (EPOC). Twenty‐two studies were included in the final evaluation. The retrieved investigations were split into studies that analysed short‐duration (until 3 h) and long‐duration (more than 3 h) EPOC. Studies that subtracted the baseline energy expenditure (EE) were analysed separately from those that did not. Most short‐duration evaluations that subtracted baseline EE reported higher EPOC for HIIE (average of 136 kJ) compared with MICE (average of 101 kJ) and higher values for SIE (average of 241 kJ) compared with MICE (average of 151 kJ). The long‐duration evaluations resulted in greater EPOC for HIIE (average of 289 kJ) compared with MICE (average of 159 kJ), while no studies comparing SIE versus MICE provided appropriate values. EE from EPOC seems to be greater following HIIE and SIE compared with MICE, and long‐duration evaluations seem to present higher values than short‐duration evaluations. Additionally, more standardized methodologies are needed in order to determine the effective EPOC time following these protocols.